Between the devil and the deep blue sea : a veteran's memoir - Queen, Khadijah (Legacy Lit, 2025)
"We stay fighting, even if we don't call it war. Between the Devil and the Deep Blue Sea is a poet's memoir about family, survival, and one servicewoman's search for autonomy. Yanked out of college and torn from her sunny hometown of Los Angeles in the early 1990s, Khadijah Queen finds herself sharing a basement apartment with her mother and sister and working two retail jobs in snowy, tiny Inkster, Michigan. Longing to escape the cycle of her family's poverty, incarceration, and addiction, she joins the US Navy, determined to earn money to finish college and make it back to L.A. on her own terms. But soon after Queen completes her grueling training and boards a doomed destroyer, she finds herself faced with near-constant sexual harassment, demeaning labor assignments, and overt racism. Stuck on a ship with nowhere to hide, she looks to poetry, literature, and letters from home to get through the long days and maintain her dignity. She keeps her head down until the workplace hostility against women spills over into her dating life and threatens to derail everything she has worked for. In trying to break through the unspoken code of silence between sailors, Queen must decide where her loyalties lie: with the Navy or within herself. Unflinching and masterfully penned, this memoir questions the promises of service to reveal the true price of being a woman at sea."--Publisher.